Quantification of the Nucleophilic Reactivities of Cyclic β‐Keto Ester Anions1. Issue 34 (30th October 2015) - Corral‐Bautista, Francisco; Mayr, Herbert
Abstract: Kinetics of the reactions of enolate anions derived from acyclic and cyclic β‐keto esters with benzhydrylium ions and quinone methides have been determined photometrically in dimethyl sulfoxide solution at 20 °C. The reactions follow second‐order rate laws: first‐order with respect to the electrophile and first‐order with respect to the enolate. Reactions conducted in the presence of 18‐crown‐6 ether and in the presence of variable concentrations of K + allowed the influence of ion‐pairing on the nucleophilic reactivities of the various enolate ions to be determined quantitatively. Enolate ions derived from oxocycloalkanecarboxylic esters show reactivities similar to those of their acyclic analogue. Enolate ions derived from δ‐lactones are less nucleophilic, which is explained by the enforced ( E ) conformation of the corresponding esters. Abstract : The configurational flexibility of acyclic β‐keto ester anions (e.g., 1 ) was partially or completely restricted by integrating them into the cyclic structures2 –4 . Kinetic investigations of the reactions of (1 –4 )‐K with benzhydrylium ions and quinone methides in DMSO allowed their nucleophilicities N to be determined, which were affected to a different extent by ion‐pairing with K + .